2022
DOI: 10.3389/fpubh.2022.1019110
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of functional dyspepsia research trends over the past 20 years

Abstract: BackgroundFunctional dyspepsia is one of the most common functional gastrointestinal disorders that affects the physical health and quality of life of many people. Its status as a chronic disease has received continued attention in the field of gastrointestinal research.ObjectiveBibliometric methods using network analysis were used to identify developments and research trends in functional dyspepsia with a view to informing and orienting further in-depth research on functional dyspepsia.MethodBibliometric meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…It has been reported that prokinetic motility drugs can alleviate the symptoms of patients with GMD by promoting gastric emptying and accommodation rates ( Shrestha et al, 2021 ). Commonly, gastrointestinal motility drugs have certain curative effects; however, all of these cause different degrees of side effects and do not effectively reduce the recurrence rate following drug withdrawal ( Wang et al, 2022 ). Traditional Chinese medicines are believed to play an important role in regulating gastrointestinal motility and alleviating GMD symptoms ( Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that prokinetic motility drugs can alleviate the symptoms of patients with GMD by promoting gastric emptying and accommodation rates ( Shrestha et al, 2021 ). Commonly, gastrointestinal motility drugs have certain curative effects; however, all of these cause different degrees of side effects and do not effectively reduce the recurrence rate following drug withdrawal ( Wang et al, 2022 ). Traditional Chinese medicines are believed to play an important role in regulating gastrointestinal motility and alleviating GMD symptoms ( Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The full record and cited references of all literature obtained from WoSCC were downloaded in TXT format [ 12 ]. The TXT files were then imported into CiteSpace (V6.3 R1 Advanced), VOSviewer (V1.6.19), and Scimago Graphica (V1.0.40) for further analysis [ 13 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The thicker the lines represent, the stronger the intensity of the association is. In addition, the colors of nodes and links manifest different clusters ( Wang et al, 2022 ; Huang et al, 2023 ). CiteSpace ( Chen, 2006 ) was applied to generate the co-occurrence and clustering map of reference.…”
Section: Methodsmentioning
confidence: 99%